Type studies in Russula 1: on two species described by Kühner. - Ruotsalainen J; Huhtinen S (Finnish Mycological Society, 2022)
Based on a detailed study of holotypes, emended descriptions of two somewhat problematic species are given. Recent material of those taxa is also presented with colour photographs. Russula nuoljae and R. purpureofusca were both described by Kühner based on one or two fruitbodies collected from Scandinavian fjelds. R. cupreola is shown to be synonymous with R. purpureofusca.